Increased duodenal iron absorption through up‐regulation of divalent metal transporter 1 from enhancement of iron regulatory protein 1 activity in patients with nonalcoholic steatohepatitis. Issue 3 (8th April 2015) - Hoki, Toshifumi; Miyanishi, Koji; Tanaka, Shingo; Takada, Kohichi; Kawano, Yutaka; Sakurada, Akira; Sato, Masanori; Kubo, Tomohiro; Sato, Tsutomu; Sato, Yasushi; Takimoto, Rishu; Kobune, Masayoshi; et al.
<x xml:space="preserve">Abstract</x> Increased hepatic iron accumulation is thought to be involved in the pathogenesis of nonalcoholic steatohepatitis (NASH). Hepatic iron accumulation, as well as oxidative DNA damage, is significantly increased in NASH livers. However, the precise mechanism of iron accumulation in the NASH liver remains unclear. In this study, 40 cases with a diagnosis of NASH (n = 25) or simple steatosis (SS; n = 15) by liver biopsy were enrolled. An oral iron absorption test (OIAT) was used, in which 100 mg of sodium ferrous citrate was administered to each individual. The OIAT showed that absorption of iron from the gastrointestinal (GI) tract was increased significantly in NASH patients, compared to SS and control subjects. Iron reduction therapy was effective in patients with NASH, who exhibited iron deposition in the liver and no alanine aminotransferase improvement after other therapies (n = 9). Serum hepcidin concentration and messenger RNA (mRNA) levels of divalent metal transporter 1 (DMT1) also were significantly elevated in patients with NASH. OIAT results were correlated with grade of liver iron accumulation and DMT1 mRNA levels. Then, we demonstrated that DMT1 mRNA levels increased significantly in Caco‐2/TC7 cell monolayers cultured in transwells with serum from NASH patients. An electrophoresis mobility shift assay showed activation of iron regulatory protein (IRP) in those cells, and IRP1 small interfering RNA clearly inhibited the increase of DMT1 mRNA levels. Conclusion: In spite of elevation of serum hepcidin, iron absorption from the GI tract increased through up‐regulation of DMT1 by IRP1 activation by humoral factor(s) in sera of patients with NASH. (Hepatology 2015) Hepatology 2015;62:751–761)